Some inequalities involving generalized hypergeometric functions via discrete Jensen’s type inequalities - Mustapha Raïssouli; Mohamed Chergui (Miskolc Mathematical Notes)
Recently, an enormous amount of effort has been devoted to extending the gamma and beta functions because of their nice properties and interesting applications. The contribution of this paper falls within this framework. We devote our attention here to investigate some approximations for a class of Gauss hypergeometric functions by the use of some discrete Jensen’s type inequalities.